(untitled) (Medico Legal Update, 2019)
Background/Objectives: This study is aimed to investigate consumers’ interests in cosmeceuticals and to examine usage and satisfaction in the aging society. Therefore, it provides effective marketing data to industries. Method/Statistical Analysis: For this study, self-questionnaires were done for Korean consumers who are in age over 20. A total of 366 copies were collected for the final analysis, and the data were analyzed by SPSS ver. 21.0 statistical program, then data were verified at the significance level of p <.05. Findings: The behavior of managing appearance healthier and younger than the actual age led to the growing in cosmeceuticals market. There are some previous studies done, but there is a lack of researches focusing on role of cosmeceuticals in the aging society. Korean consumers’ knowledge about skin was relatively high with an average score of 79.0%. However, the result of analyzing perception of cosmeceuticals proved that the definition of cosmeceuticals was not widely known, and there was lack of promoting cosmeceuticals to general consumers: 23.2% used cosmeceuticals without being aware of them. The strength of cosmeceuticals was high reliability due to its professionalism, and the drawback was its high cost. So, for the development of cosmeceutical market, it is necessary to introduce a marketing method which can reduce its cost. Many Korean consumers used cosmeceuticals with moisturizing effect, and the overall satisfaction level was 3.59 out of 5.00. Especially, the satisfaction level was high with the use of cosmeceuticals of anti-wrinkle or moisturizing effects. Improvements/Applications: This study will provide the effective marketing resource to beauty industries and propose a positive direction to expand cosmeceutical market in the aging society.